2018
DOI: 10.1186/s12862-018-1175-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the Asian lineage dengue virus type 3 genotype III in Malaysia

Abstract: BackgroundDengue virus type 3 genotype III (DENV3/III) is associated with increased number of severe infections when it emerged in the Americas and Asia. We had previously demonstrated that the DENV3/III was introduced into Malaysia in the late 2000s. We investigated the genetic diversity of DENV3/III strains recovered from Malaysia and examined their phylogenetic relationships against other DENV3/III strains isolated globally.ResultsPhylogenetic analysis revealed at least four distinct DENV3/III lineages. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
2
13
1
Order By: Relevance
“…In the present study, the DENV-3 genotype III tMRCA was estimated (based on envelope-encoding sequences) to be 1949 (95% HPD: 1936.1–1963.6), consistent with the previous study [ 73 ]. However, this value (again, obtained based on envelope-encoding sequences) differed from the tMRCA of 1967 (95% HPD: 1965–1969) reported by Tan et al [ 74 ] based on analysis of the complete viral coding sequence. This difference might be due to the fact that the oldest virus in our analysis was from 1966 (JQ868069) and represented an isolate from which only the envelope sequence was available.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In the present study, the DENV-3 genotype III tMRCA was estimated (based on envelope-encoding sequences) to be 1949 (95% HPD: 1936.1–1963.6), consistent with the previous study [ 73 ]. However, this value (again, obtained based on envelope-encoding sequences) differed from the tMRCA of 1967 (95% HPD: 1965–1969) reported by Tan et al [ 74 ] based on analysis of the complete viral coding sequence. This difference might be due to the fact that the oldest virus in our analysis was from 1966 (JQ868069) and represented an isolate from which only the envelope sequence was available.…”
Section: Discussioncontrasting
confidence: 79%
“…Outside of Thailand, DENV-3 genotype III also has been disseminated to other countries in Asia. DENV-3 genotype III was isolated as a minor genotype in Laos in 2012–2013 [ 76 ], and was first observed in Vietnam in 2013 [ 77 ], in Singapore in 2013 [ 78 ], and in Malaysia in 2008–2010 [ 74 ]. Our study revealed that the DENV-3 genotype III currently circulating in Thailand clusters with lineage-C viruses from South Asia (India and Pakistan) and from other areas in Southeast Asia (Singapore, Laos, and Viet Nam) where the virus had been detected; this cluster was independent of the lineage-A viruses (recovered from Sri Lanka, Malaysia, and Singapore) and the lineage-B viruses obtained in the Americas.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though it was proposed that the hyperendemicity could aggravate the frequency of dengue severe symptoms, the relationship between concurrent infection and disease severity remain contradictory, with variable conclusions depending on the studies [17]. The co-circulation and the replacement of genotype are also associated with virulence and have already been reported [1821]. In Thailand, genotype replacement for DENV-2 and DENV-3 was reported during the 1980’s and the 1990’s, respectively [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…However, patterns of inapparent infection rates are heterogenous, further confounding efforts to estimate transmission intensity [151][152][153][154][155]. While cost-effective and easyto-use rapid diagnostics exist for DENV, a lack of specific and consistently performing diagnostics contributes to this problem, especially in regions where genetically related viruses cocirculate, leading to misclassification of positive results [156][157][158][159][160][161][162][163][164][165][166][167][168][169]. Diagnostic tools for tickborne diseases relevant to the region are nonexistent, and this has hampered confirmation of infection, identification of pathogen, and conduct of surveillance.…”
Section: Understanding the Eco-environmental Drivers Of Transmissionmentioning
confidence: 99%